Media, Evil and Society. Media Use and its Impacts on Crime Perception, Sentencing Attitudes and Crime Policy (Archives of Criminology, 2006)
ln democratic societies, crime policy and its management by parliaments and ministries largely depends on trends in crime. If, over a prolonged period. the media report strong upward trends in the number of crimes committed and if the public clebate on crime focuses on spectacular, serious crimes, policymakers come under heavy pressure to increase statutory punishments and tighten the rules of procedure for criminal prosecutions. The courts in turn feel bound to hand out tougher sentences – passed in the name of the people, their judgements are meant to reflect public opinion. The question thus arises as to whether long periods of either dwindling or stable crime figures allow policymakers and the courts to soften punishments for specific offences and to place, for example, the notion of offender-victim compensation and offender resocialisation at the forefront.There is thus every reason to raise awareness of the relationship between the media and the perceptions of crime. The German Police Crime Statistics for the last 10 years indicate a strong downward trend in the number of crimes that people perceive as very threatening or generally worrying. There has been a 45 percent reduction both in the number of break-ins in private homes and in bank robberies. In the past l0 years, the number of murders has dropped by around 41 percent. Car thefts are down by as much as 70 percent. While other offences like fraud have increased, there has been a slight overall reduction in the number of crimes recorded since 1993. In the light of our ageing society, this hardly comes as a surprise. In the past decade, the 18 to 30 age group - a group which in 1993, for example, made up almost half of all crime suspects - has shrunk from 9.4 to 7 percent of the population. Conversely, there has been a strong increase (from 20.4 to 24.4 percent) in the numer of people aged 60 and over a group that accounts for less than 3 percent of all violent crime suspects. Germany's ageing society is evidently good for domestic security. Another significant preventive effect is the stabillsation in migration since 1993.Positive trends of the type indicated for the last 10 years can, of course, only influence crime policy if they shape the public debate on crime and are made known to a broad majority of the population. But this is not always the case. Whether or not crime is on the increase or the decrease is not usually something most people are aware of. Unlike the rise and fall of fuel prices that we can all observe at local filling stations, crime is a social phenomenon that often happens out of public view. Even when crime occurs in public, say graffiti spraying on the walls of buildings, drug dealing in open spaces, and mass hooliganism among drunken football fans, even those who regularly observe such events can at best estimate their frequency based on the world they see. The limited geographical scope of their personal experience does not allow them to make a reliable assessment of trends in the occurrence and the gravity of such offences. This is certainly the case as regards serious crimes that occur less frequently. In assessing the situation, members of the general public must rely entirely on what is reported by the mass media. The question arises, therefore, as to how people perceive current trends in crime and what role the media play in influencing their judgement.